2017
DOI: 10.1116/1.4978026
|View full text |Cite
|
Sign up to set email alerts
|

Real-time growth study of plasma assisted atomic layer epitaxy of InN films by synchrotron x-ray methods

Abstract: The temporal evolution of high quality indium nitride (InN) growth by plasma-assisted atomic layer epitaxy (ALEp) on a-plane sapphire at 200 and 248 °C was probed by synchrotron x-ray methods. The growth was carried out in a thin film growth facility installed at beamline X21 of the National Synchrotron Light Source at Brookhaven National Laboratory and at beamline G3 of the Cornell High Energy Synchrotron Source, Cornell University. Measurements of grazing incidence small angle x-ray scattering (GISAXS) durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Illustrations of a typical scattering geometry and scattering pattern are shown in Figure a and b, in which the scattering intensity is described as a function of in-plane and out-of-plane momentum transfer, q y and q z , respectively. GISAXS studies of ALD processes have been reported for a broad range of material systems, including various metals, oxides, , and nitrides. …”
Section: Working To Understand Inn Growth By Aldmentioning
confidence: 99%
See 2 more Smart Citations
“…Illustrations of a typical scattering geometry and scattering pattern are shown in Figure a and b, in which the scattering intensity is described as a function of in-plane and out-of-plane momentum transfer, q y and q z , respectively. GISAXS studies of ALD processes have been reported for a broad range of material systems, including various metals, oxides, , and nitrides. …”
Section: Working To Understand Inn Growth By Aldmentioning
confidence: 99%
“…Researchers at the U.S. Naval Research Laboratory have reported several in situ GISAXS studies of InN plasma ALD growth kinetics. The most significant results are summarized and discussed here. The experiments were performed in the G3 hutch of the Cornell High Energy Synchrotron Source using a custom plasma ALD system with an ICP source, X-ray-transparent beryllium windows, and air-cooled dry vacuum pump.…”
Section: Working To Understand Inn Growth By Aldmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the context of the 3D growth morphology, the mounded configuration is very stable after this point. Nepal et al 34 suggested that around 2-unit cell thickness, corresponding to 4 layers, the substrate surface is more than 50% covered by the film and the mound structure stabilizes. These experiments provide direct evidence for the latter part of that supposition.…”
Section: Resultsmentioning
confidence: 99%
“…An individual PE-ALD cycle is explained schematically in Figure . Under the experimental conditions, it takes 8–10 PE-ALD cycles to form a monolayer of wurtzite InN, with a monolayer being half a unit cell height. , …”
Section: Resultsmentioning
confidence: 99%